Sociological characteristics of basketball players in 3 competitive levels - Vuckovic, I.; Mekic, M. (Homosporticus, 2008)
Based on up to now researches on sociological characteristics of basketball players, as well as the sportsmen generally, this research had an aim to establish and analyze the differences between basketball players of three competitive levels in their sociological characteristics. Participants Sample (n=113) was formed of 38 players from Premier league of Bosnia and Herzegovina (M=26 yrs, SD=4.1 yrs), 37 players from the First league of entity Republic of Srpska (M=22.5 yrs, SD=2.5 yrs) and 38 players from the Second league of entity Republic of Srpska (M=18.5 yrs, SD=1.7 yrs). Modified survey SSMAXIP (Hošek, 2004) was used as an instrument of this research. There were found significant differences between groups (ANOVA) in the majority of measured variables. The most significant difference was found in criterion of socially-economical factor, then the family factor, while the least significant difference found amongst groups was in criterion of educational factor. Results suggest that the influence of sociological factor on basketball players` success is evident.